In Vitro Regeneration of Ragleaf (Crassocephalum crepidioides (Benth.) S.Moore) Using Kinetin - Abdulsalam, Murtadha, Mosobalaje; Olanike, Oladejo, Omobolanle (PLANTA TROPIKA, 2024)
Micropropagation is a valuable means for large-scale production and preservation of invasive alien species such as ragleaf. To determine the concentration of kinetin adequate for in vitro growth of the ragleaf flower, seeds of the plant were propagated in vitro using Murashige and Skoog medium supplemented with basal 0.5 mg L-1 Naphthalene Acetic Acid and incubated for four weeks. The growing shoots were cut into pieces and inoculated into MS media with five kinetin concentrations: 0.0, 1.0, 1.5, 2.0, and 2.5 mg L-1. The tubes were kept in an incubation room for seven weeks. The experiment was arranged in a completely randomized design with ten replications. Shoot length (cm) and the number of leaves, nodes, and roots were measured. The control medium recorded less growth performance across all the variables, indicating the important role of the exogenous kinetin. The plants in 2.50 mg L-1 kinetin were the tallest (7.23±0.87 cm) with the highest number of leaves (28.17±2.57), nodes (10.50±1.02) and shoots (3.83±0.17). The media containing 2.50 mg L-1 kinetin also produced the highest number of roots (9.00), which is necessary for the survival of the seedlings. The results indicate that 2.5 mg L-1 is adequate for cultured C. crepidioides.